Comparative Study of Effectiveness of Clindamycin Monotherapy and Clindamycin - Benzoyl Peroxide Combination Therapy in Grade II Acne Patients - M, Apoorva D; C, Sharath Kumar B; K, Vanaja (Indian Journal of Pharmacy Practice)
Background: Acne vulgaris is a chronic inflammatory disorder of pilosebaccous follicles affecting more than 85 percent of adolescents and young adults. Topical clindamycin inhibits Propionibacterium acnes and provides comedolytic as well as anti-inflammatory activity, in combination with Benzoyl Peroxide (BPO). Clindamycin in combination with benzoyl peroxide has been reported to reduce the emergence strains of Propionibacterium acnes that are less sensitive to antibiotics, which would help in optimizing efficacy in the management of mild to moderate acne vulgaris. Aim: To compare the efficacy of combination of Clindamycin and Benzoyl Peroxide versus Clindamycin alone in the treatment of mild to moderate acne vulgaris in grade II acne patients. Methods: Eighty patients were randomly allocated in to two groups of 40 each to receive topical Clindamycin (Group A) and Clindamycin-Benzoyl Peroxide (Group B), with evaluation at 2nd, 4th and 6th week follow up. Efficacy parameters of Non-Inflammatory and Inflammatory lesion count and safety parameters such as erythema, dryness, burning and pruritis were also measured. Dermatologist perception along with patient's response towards the treatment was also observed. Result: Mean age of the patients was within the age group of 21-25 years. Females constituted about 77.5% and 22.5% were males. Clindamycin showed 25.05% and 28.4% improvement and Clindamycin-Benzoyl Peroxide combination showed 75.17% and 78.3% improvements in Non-Inflammatory and Inflammatory lesion counts. Erythema, dryness, burning and pruritis were observed in both the groups, and was gradually reduced by week 6. Conclusion: Our data suggested that, Clindamycin-Benzoyl Peroxide combination is an effective topical agent in the treatment of patients with mild to moderately acne.
Keywords: Acne; efficacy; safety; Clindamycin-Benzoyl peroxide; Monotherapy; Combination Therapy; Non-Inflammatory; Inflammatory lesion count